Parenting intervention outcomes for kinship caregivers and child: A systematic review. (August 2020) - Wu, Qi; Zhu, Yiqi; Ogbonnaya, Ijeoma; Zhang, Saijun; Wu, Shiyou
Abstract: Background: Kinship foster caregivers often face serious challenges but lack adequate parenting capacities and resources. The importance of parenting interventions for kinship foster caregivers has been recognized, and researchers have assessed the effect of various parenting interventions on the caregivers and children. However, no systematic review has been conducted to summarize findings related to parenting interventions targeting kinship care. Objectives: This study systematically summarizes the effect of parenting interventions on kinship foster caregivers and their cared for children, and examines the intervention strategies and research methods used in order to provide a context in which to better understand effects of interventions. Methods: From six academic databases, 28 studies were identified for review. A data template was used to extract the following information from each study: intervention targets, research design, settings, intervention description, outcome measures, and main results for each study. Results: Various parenting interventions targeting kinship foster care families have been developed to improve parenting capacities and reduce parental stress. Most of the interventions had a positive impact on the outcomes of both caregivers and children, although the assessed outcomes often differed across studies. Parenting interventions improve caregivers' parenting competency, reduce parental stress, and advance child wellbeing. However, some interventions appear less promising in achieving targeted goals. Discussion: The findings suggest that promoting evidence-based parenting interventions with a special focus on kinship care is important for child welfare. Future directions for research are also discussed in this study.